Anglo-Saxon deviant burial customs - Reynolds, Andrew (Oxford University Press, 2009)
Sources, approaches, and contexts – Burials, bodies, and beheadings : interpretation and discovery – Social deviants in a pagan society : the fifth to seventh centuries – Social deviants in a Christian world : the seventh to eleventh centuries – The geography of deviant burial in Anglo-Saxon England – Themes and trajectories : the wider social context
9780199544554
Keywords: Anglo-Saxons; Deviant behavior; Funeral rites and ceremonies